Evaluation of certain udder traits in Hungarian Lacaune herds - Kapusi, Vivien Bianka; Gulyás, László; Gergátz, Elemér; Póti, Péter; Tóth, Gábor; Pajor, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The aim of this study was to investigate the udder conformation traits of Lacaune ewes in two herds, in three consecutive years. Estimated heritability of udder conformation traits in most of the cases was medium or good, therefore these traits can be improved significantly even in some generations. Three years selection for udder traits resulted in significant improvement in a dairy population, visible in the increase of udder scores.According to our results, Lacaune breed should be more widespread, used even as a crossing partner for improving udder traits in dairy populations, through which milk production of ewes could improve - in quantity and quality as well - making the Hungarian sheep sector more profitable.
Keywords: udder; Lacaune; selection; milk production